Pay As You Earn (PAYE) Tax as Panacea to Backlog of Gratuities and Pensions of Civil Servants in Nigeria - Sani Mohammed; Sunusi Garba; Armaya’u Alhaji Sani; Rukayya Tijjani Ibrahim; Yusra Musa Muhammad; Ibrahim Ahmad Kassim (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Gratuities and pensions are payments due to retired civil servants; however, payments of these have not been timely and consistent to the extent that 23 state governments are owing N836.40 billion as gratuities and pension liabilities as of the end of 2022. Non-payment of these retirement benefits is often accompanied by social and health problems, leading to the premature death of retirees. Consequently, this study aims to examine the potential of monthly Pay As You Earn (PAYE) tax to eliminate the backlog of retirement benefits owed to retired civil servants. To achieve this aim, quantitative secondary data of PAYE tax collections by state governments is collected from the annual Internally Generated Revenue reports of states published by the National Bureau of Statistics (NBS) 2010-2022. Descriptive statistical analysis tools are employed to analyze collected data while Burgess’s activity theory and public policy analytical framework guided the conduct of the study. On the overall, results from the study revealed that while the 23 state governments owe N836.40billion as liabilities of retirement as at 2022, the same states have collected the sum of N5,672billion as PAYE tax 2010-2022. On individual states, 20 states have collected PAYE tax 2010-2022 more than their liabilities of retirement benefits, while only three states collected PAYE tax less than their accumulated liabilities of retirement benefits. The short-run policy implication is for states to set aside collected PAYE tax to settle the backlog of benefits and adopt the Contributory Pension Scheme (CPS) to avoid future recurrence of the backlog